Ratio Decidendi Status hukum anak hasil Surrogate Mother persepektif Fiqh dan Hukum Positif di Indonesia - M. Fahmi Afif (SHAKHSIYAH BURHANIYAH: Jurnal Penelitian Hukum Islam, 2025)
Abstract Married couples must want to have offspring. However, it is not uncommon for couples to not be blessed with children due to several factors. The development of the increasingly advanced world of medicine offers several solutions for the occurrence of pregnancy, including IVF and uterine leasing or known as Surrogate Mother. then the question arises about the legal status of a child produced from uterine leasing born, because in civil law about the position of children only recognise children - legitimate children and illegitimate children. this research uses normative legal research methods using two approaches, conceptual approaches and comparative approaches. The result of this research is that the legal status of children of womb rental according to Islamic Law is invalid because it is not possible to exit and enter the sperm in a muhtaram which is a requirement for the bernasab of a child to his father. And according to Indonesian law, children from uterine leases are invalid because they are not produced from a legal marriage. whether the marriage is valid or not returns to religious norms as the principle of marriage in Indonesian law.